Comparison of alfaxalone, ketamine and thiopental for anaesthetic induction and recovery in Thoroughbred horses premedicated with medetomidine and midazolam. (6th February 2016) - Wakuno, A.; Aoki, M.; Kushiro, A.; Mae, N.; Kodaira, K.; Maeda, T.; Yamazaki, Y.; Ohta, M.
Summary: Reasons for performing study: There is limited information on clinical use of the new injectable anaesthetic agent alfaxalone in Thoroughbred horses. Objectives: To compare anaesthetic induction and recovery characteristics and cardiopulmonary responses between alfaxalone, ketamine and thiopental in Thoroughbred horses premedicated with medetomidine and midazolam. Study design: Randomised blinded experimental cross‐over study. Methods: Six Thoroughbred horses were anaesthetised 3 times with alfaxalone 1 mg/kg bwt, ketamine 2.5 mg/kg bwt or thiopental 4 mg/kg bwt after premedication with medetomidine 6  μ g/kg bwt and midazolam 20  μ g/kg bwt. Qualities of anaesthetic induction and recovery were scored on a scale of 1 (poor) to 5 (excellent). Induction time and recovery time were recorded. Cardiopulmonary values (heart rate, respiratory rate, arterial blood pressures, and arterial blood gases) were recorded throughout anaesthesia. Data were analysed with nonparametric methods. Results: The anaesthetic induction (P = 0.2) and recovery (P = 0.1) quality scores (median, range) were not different amongst protocols and were 4.0, 3–5; 5.0, 4–5; 4.5, 3–5; and 4.5, 3–5; 3.5, 2–5; 4.0, 2–5 for alfaxalone, ketamine and thiopental, respectively. Induction time for ketamine (67, 53–89 s) was significantly longer than that for alfaxalone (49, 40–51 s, P = 0.01) and thiopental (48, 43–50 s, P = 0.01). Time to standing for alfaxalone (44, 40–63 min, P = 0.01) and thiopental (39, 30–58 min, P = 0.01) was significantly longer than that for ketamine (25, 18–26 min). Cardiovascular values were maintained within the clinically acceptable level throughout anaesthesia. Respiratory rate significantly decreased during anaesthesia for all 3 drugs; however, spontaneous breathing did not disappear, and PaCO2 values were maintained at approximately 50 mmHg. Conclusions: All 3 drugs showed similar effects in relation to anaesthetic induction and recovery qualities and cardiopulmonary responses. However, alfaxalone and thiopental prolonged recovery time compared with ketamine.